Integrated geophysical methods for ground water prospecting in fault fracture zones under low-resistivity background conditions: a case study from Laohutiangou Village, Xuanwei, Yunnan Province - Zheng, Zhijie; Yan, Jiayong; Zeng, Jie; Gan, Fuping; Liu, Wei; Lu, Xiuhua (Earth science informatics, 2025)
The fault fracture zone is closely related to groundwater activity, which is a common target for water exploration and well drilling. It is often located below the cover layer, which is difficult to identify solely through geological surveys due to its concealment. Geophysical methods are a common and effective means of quickly identifying fault fracture zones. The fault fracture zones and the developed fissures within them often manifest as low-resistivity anomalies. When under low-resistivity background conditions, the identification difficulty of the fault fracture zone increases. A single geophysical method often has ambiguity and uncertainty in identifying fault fracture zones. Therefore, this paper uses integrated geophysical methods to determine the location, depth, and properties of a fault fracture zone and further assess it based on geological data, achieving good results. First, electrical resistivity tomography is used to determine the approximate location and range of the fault fracture zone. The abnormal feature is a low-resistivity strip with a localized low-resistivity trap. The low-resistivity trap area is a concentrated zone of fault fracture with fractured lithology. The audio-frequency magnetotelluric method is used to determine the depth of the bottom boundary of the fault fracture zone The anomalous feature presents a wide and gentle U-shaped low resistivity. The drilling depth is determined by inferring the depth of the bottom boundary of the fault fracture zone using the audio-frequency magnetotelluric method. The composite profiling method is used to accurately locate the fault fracture zone and determine the drilling position. The anomalous feature is determined to be a synchronous low-resistivity anomaly, which changes from a V-shaped to a U-shaped from shallow to deep. As the electrode distance increases, the inferred width of the fault fracture zones change from narrow to wide. To reduce the ambiguity and uncertainty in identifying fault fracture zones in low-resistivity environments using conventional electrical and electromagnetic methods, the microtremor horizontal-to-vertical spectral ratio (HVSR) method is used to further review the location of the fault fracture and fissure zones. The abnormal feature is a horizontal-to-vertical (H/V) high-value trap. The apparent resistivity sounding curve is used to determine the burial depth of water-bearing fissure zones in the fault fracture zone. The anomalous feature is a V-shaped low-resistivity anomaly. Then, the water content of the hanging and foot walls of the fault based on hydrogeological conditions is analyzed. Finally, on the basis of the construction site conditions, a drilled hole is performed near the fault fracture zone (342.5 measuring points), with a depth of 160.3 m. When the water level drawdown is 6.90 m, the water inflow is 107.40 m 3 /day. After drilling verification, the selection and application process of the above method is a scientifically reasonable water exploration model that can be applied to the same geological background conditions. The case study results show that the combination of geophysical prospecting methods, namely, electrical resistivity tomography, audio-frequency magnetotelluric method, composite profiling method, microtremor HVSR method and apparent resistivity sounding curve can effectively explore the fault fracture zones under low-resistivity background conditions.